Bioaccumulation of dioxin-like PCBs and PBDEs by detritus-feeding fish in the Rio de la Plata estuary, Argentina - Cappelletti, Natalia Elsa (2015)
A comparative analysis of bioaccumulation behavior of dioxin-like polychlorinated biphenyls (dlPCBs) and polybrominated biphenyl ethers (PBDEs) was conducted involving simultaneous measurements in settling particles and a detritivorous fish (Sabalo, Prochilodus linneatus) collected in the sewage impacted Buenos Aires coastal area. Focalization of dlPCBs and PBDEs along the detritus food chain is reflected by a 30–40-fold increase of dry weight PBDE and dlPCB concentrations from settling particles to fish (1.8 ± 1.0 to 58 ± 31 and 6.8 ± 3.9 to 281 ± 155 ng g−1 dry weight (dw), respectively). In this transference, dlPCB congeners presented more conservative patterns than those of PBDEs, basically due to debromination of BDE 99 and 153 to BDE 47 in fish. Lipid/organic carbon-based biota-sediment accumulation factors (BSAFs) ranged between 5 and 20 (7.3 ± 3.0 and 16 ± 8.0 for PBDEs and dlPCBs). Congener-specific BSAF of dlPCBs suggested a lower bioavailability of more planar non-ortho-PCB versus mono-ortho-PCB suggesting higher affinity to organic matter. BSAFs of PBDEs differed markedly among bromine homolog groups, supporting the biotransformation-formation from higher brominated to lighter congeners. The log BSAFs-log KOW relationship of dlPCBs and PBDEs presented a parabolic pattern maximizing at log KOW 6–7, but PBDE curve differs reflecting biotransformation processes.